Evaluating Gender Based Behavior in Historical Urban Public Place Case study: Grand Bazaar, Kerman, Iran - Aida Jalalkamali; Elham Anjomshoa (Alanya Hamdullah Emin Paşa Üniversitesi, 2019)
The study evaluates the spatial behaviors of women in urban public place through ‘fear of crime’ and ‘public place functionality’ factors; by using direct observations and questionnaire within the Grand Bazaar as a historical urban public place in the center of Kerman, which is located in the Southwest part of Iran. The study provides a particular perspective to the analysis and understanding of how women make decisions and behave in a spatial setting based on environmental psychology studies. This study applies combinational research methods including qualitative and quantitative approach, including analytical, descriptive, correlation, and logical reasoning methods. This study also conducts direct observation in order to search the strengths and weaknesses of Grand Bazaar as a public place. The results of the study reveal that there is a significant correlation between fear of crime and women’s environmental perception of Grand Bazaar. Furthermore, the research findings indicate that the anxiety of being in less crowded parts of Bazaar is more tangible among women than men. On the other hand, the results show there is a significant correlation between time periods and women’s activities in Grand Bazaar.